Mental Health in 3D: A Dimensional Model of Mental Illness Representation in Digital Games - Dunlap, Kelli; Kowert, Rachel (Loading, 2021)
There is a wealth of research on the depiction and impact of mental health representations in traditional media; however, less is known about video games. As the dominant form of media in the 21st century, video games uniquely portray mental illness in traditional ways as well as in ways unique to video games, such as in-game mechanics (e.g., sanity meters) and player-driven decision making. This paper outlines the importance of cultural messages relating to mental illness as conveyed through video games in terms of content and influence and presents a multi-dimensional model of analysis for the representation of mental illness in digital games. The aim of this paper is to provide a foundation for understanding how mental illness is represented in digital games, provide a new perspective for thinking critically about representation of mental illness in games, and overview a new framework for assessing video game content in this area.